(3CfHGA Gdjef hfHdGDgs - (3YHO Gddg Hf YHO GdcQje GdLQGajs
(3ChdgG (B:s
(3Chdg eHJhQ hChd GdehLhO efg CKfGA CMOGK SfI (B1210 (3g` bhdg (B: (3hajgG ef fHdGA Gdjef GdSjO GdYdGeI GdMGaX eMeO Hf eMeO GdRHjOi GdMfai , CHh GdajV GdeYQha HGdSjO eQJVi Jhai Yf SJjf SfI HeUQ s
(3BNQgG (B:s
(3BNQg HYfhGf (B" (3hef Cge MhGOKg aJM JQYI GdShjS ai SfI (B1386 (3g` bhdg (B: (3hHdZJ GdZQGeI ai GdfabI Ydi MaQ GdJQYI YTQjf Cda LfjI GfJgi edNUkG s
(3GdfSNI HgG MhGTs
(3cJHJ GdYfhGfGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs